Determinación de Calidad del Agua de los Ríos Mongas y Machángara, ubicados dentro del Distrito Metropolitano de Quito, utilizando la metodología estadística del índice Universal de Calidad de Agua (uwqi), del periodo 2016- 2019. - Plasencia Santafe, Cynthia Margoth (2020)
In the present investigation work of , the study of the water quality index of the Monjas and Machángara Rivers located within the Metropolitan District of Quito in the period 2016-2019 was carried out, through the application of the UWQI (Universal Water Quality Index) methodology, considering two climatic seasons of raining and drying season for each year, the collection and consolidation of the data base was carried out through the documental investigation with the use of technology and digital platforms, obtaining scientifically supported data from the existing files in the National Secretariat of the Environment (2020), the statistical analysis was carried out through the box diagrams visualizing the degree of dispersion of the magnitude of each physical-chemical parameter considered in the study, analyzing the reason of the outliers produced by some extraordinary event in time; through the calculation methodology, the water quality index was determined for each year and time of study, qualifying according to the category that the quality indicator and warning signal take in a period of 0 to 1 for the indicated use, the results were tabulated and compared presenting the values in graphic form for a better analysis and interpretation, reflecting as a final result with the best water quality in the general study period the Machángara River in the two climatic conditions with a maximum quality value of 0.55 with a regular rating compared to the Monjas River showing a lower water quality with a minimum value of 0.43 with a bad rating evidencing severe contamination in said tributary.